Effect of strain energy on corrosion behavior of ultrafine grained copper prepared by severe plastic deformation - Rifai, Muhammad; Mujamilah, Mujamilah; Bagherpour, Ebad; Miyamoto, Hiroyuki (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Effect of strain energy on corrosion behaviour of ultrafine-grained (UFG) copper prepared by severe plastic deformation was investigated in term of microstructural evolution. Pure copper was processed by simple shear extrusion (SSE) for two, four, eight and twelve passes. The structure of SSE treated sample was observed by laser microscope and transmission electron microscope as well as X-ray diffraction, The corrosion behaviour by potentiodynamic polarization curve was observed modified Livingstone solution, NaCl and sulphuric solution. The structure of SSE processed showed that the dislocation density and micro strain increased by the pass number up to eight passes; on the other hand, the crystallite size decreased. After twelve passes, the dislocation density decreased due to homogeneous structure and small grain; it also related to corrosion behaviour of UFG copper. The modified Livingstone and NaCl solution affected to grain boundaries and dislocation inside the grain